2011
DOI: 10.1002/jsfa.4464
|View full text |Cite
|
Sign up to set email alerts
|

Shrimp shell peptide hydrolysates inhibit human cancer cell proliferation

Abstract: The promising anticancer peptide fractions from shrimp waste proteins has the potential for novel nutraceutical ingredient applications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(28 citation statements)
references
References 14 publications
0
28
0
Order By: Relevance
“…Several studies have demonstrated the antioxidant potential of protein hydrolysates from many raw materials, such as potato (Wang & Xiong, 2005), whey (Contreras et al, 2011), soy (Peña-Ramos & Xiong, 2003), fish (Dekkers et al, 2011), and shrimp waste (Dey & Dora, 2014). Furthermore, a study has shown that shrimp shell hydrolysates can inhibit human cancer cell proliferation (Kannan et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have demonstrated the antioxidant potential of protein hydrolysates from many raw materials, such as potato (Wang & Xiong, 2005), whey (Contreras et al, 2011), soy (Peña-Ramos & Xiong, 2003), fish (Dekkers et al, 2011), and shrimp waste (Dey & Dora, 2014). Furthermore, a study has shown that shrimp shell hydrolysates can inhibit human cancer cell proliferation (Kannan et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, T1 had an IC 50 value of 77.29 lg/mL or 81.91% of inhibition at 500 lg/mL on HepG-2, and 34.7% of inhibition at 500 lg/mL on MCF-7 (an IC 50 value not available); T2 had an IC 50 value of 237.64 lg/mL or 70.65% of inhibition at 500 lg/mL on HepG-2, and an IC 50 value of 214.11 lg/mL or 73.7% of inhibition at 500 lg/mL on MCF-7. Thus, for inhibitory effect on HepG-2, T1 and T2 were better than the reported hydrolysates: shrimp shell peptide fractions (60% of inhibition at 1 mg/mL) (Kannan et al, 2011), Nemipterus japonicas hydrolysate (an IC 50 value 48.5 mg/mL) and Exocoetus volitans hydrolysate (an IC 50 value 21.6 mg/mL) (Naqash and Nazeer, 2010); for inhibitory effect on MCF-7, T1 and T2 were better than cod hydrolysates (40% of inhibition at 1 mg/mL) (Picot et al, 2006), but weaker than squid skin hydrolysates (an IC 50 value <0.13 mg/mL) (Aleman et al, 2011). Notably, on HepG-2, the IC 50 value of T1 (77.29 lg/mL) was lower than that of 5-FU (136.27 lg/mL), and on MCF-7 the IC 50 value of T2 (214.11 lg/mL) was similar to that of 5-FU (245.82 lg/mL).…”
Section: Discussionmentioning
confidence: 60%
“…However, due to the existence of gastric acids and complex enzymes in the gastrointestinal environment, bioactive peptides are easily degraded (Kannan et al, 2011). One possible approach is the encapsulation of bioactive peptides, which can be protected against degradation in stomach and pass through the intestinal barrier to enter the blood stream for absorption (Kaya-Celiker and Mallikarjunan, 2012).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Shrimp shell peptides (<10 and 10–30 kDa peptide fractions), low molecular weight chitin, Penaeidin‐2 antimicrobial peptide and haemocyanin showed antitumoral activities (Kannan et al . ; Salah et al . ; Meng et al .…”
Section: Shrimp Micrornas With Antitumoral Activity: An Alternative Smentioning
confidence: 99%